Polyhydroxyalkanoates As Reserve Materials For Survival During Nutrient Starvation And Enhanced Tolerance Towards Oxidative Stress - Goh, Lay Koon (2008)
Delftia acidovorans DS 17 was used to study the roles of polyhydroxyalkanoates (PHAs) in enhancing starvation survival and oxidative stress tolerance of the cells.